Integrating the Theory of Planned Behavior and Consumer Trust to Explain Millennials’ Behavioral Intentions toward Green Café Spaces in Urban Jakarta - Nur Fitriyani, Wakhidah; Djumarno, Djumarno (International Journal of Indonesian Business Review, 2025)
Purpose – This paper seeks to examine the influence of the Theory of Planned Behavior (TPB)—including Attitude Toward Behavior, Subjective Norms, and Perceived Behavioral Control—on Millennials’ Behavioral Intention toward visiting green café spaces in urban Jakarta, with Consumer Trust as a mediating variable. Methodology/approach – A quantitative survey method was used to collect data from 150 Millennial respondents residing in Jakarta. The questionnaire measured TPB constructs and Consumer Trust. Data were analyzed using Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 to evaluate direct and mediating effects. Findings – The study found that Attitude Toward Behavior significantly influences both Consumer Trust and Behavioral Intention, while Subjective Norms significantly influence Behavioral Intention only. Perceived Behavioral Control significantly affects Consumer Trust, but not Behavioral Intention. Furthermore, Consumer Trust does not significantly influence Behavioral Intention, and all mediating effects through Consumer Trust were also not supported. These results suggest that direct TPB components—especially attitude and social norms—are stronger predictors of Millennials’ intention to visit green cafés than trust-based indirect paths. Novelty/value – This study extends the TPB framework in the context of sustainable consumption by highlighting that trust may not directly drive behavioral intentions in early-stage environmental decisions. It offers insights for businesses seeking to promote green cafés and engage urban Millennial consumers through personal and social behavioral strategies.